Growth and yield response of wheat ( Triticum aestivum L) to nutritional application of nitrogen and KSB levels. (International Journal of Food and Nutritional Sciences, 2022)
A field experiment of present investigation was executed at the research farm , Department of Agronomy ,Faculty of Agriculture Science and Technology ,AKS university , Sherganj , Satna ., MP during Rabi season , 2021 . This experiment was executed in randomized Block design with factorial concept adopting three replications. Twelve treatment combinations were evaluated including four levels of nitrogen i.e. ( 0 kgN / ha , 80 kg N/ha , 100kg N/ha and 120 kgN/ha and KSB levels were 0.5 lit./ha ,lit/ha and 1.5 lit. /ha ) . Individual incorporation of nitrogen and KSB could cause tremendous increase in growth as well as yield of wheat crop. Maximum values in wheat were recorded in height of the plant ( 81.59), number of leaves per plant ( 238.89 ), number of tillers per meter row (66.22 ), length of spike (8.98 cm ), number of grain per spike (37.51 ) , test weight (39.98g ), grain yield (47.51 q /ha )and straw yield (75.18 q/ha )when 120 kg nitrogen /ha was incorporated. Similarly KSB also brought paramount effect on above growth as well as yield and yield attributes of wheat crop . Interactive effect of nitrogen and potassium soluble bacteria was also positive and all the growth and yield and yield attributes were affecting favorably Maximum values with respect to these parameters were noted in height of the plant (89.04 cm ) , number of leaves per plant (255.53 ) , number of grains per spike (38.27 )test weight (41.79 ) , grain yield (49.03 q/ha ), straw yield (76.64 q/ha )when combined use of 120 kg nitrogen and 1.5 li/ha was done.